Legal Analysis of a U.S. Women’s Soccer Team Suing the Federation Over Alleged Gender Discrimination - nastiti hayuningtyas; diva anindia putri afriani; mahlita salsa delselaningtyas (Indonesian Journal of Sports Law, 2025)
The United States Women's National Soccer Team (USWNT) lawsuit against the U.S. Soccer Federation has opened a new discourse on the limits of sports federation autonomy before state law. This study aims to analyze gender discrimination practices in the form of wage disparities and unequal facilities as a violation of the basic rights of athletes who deserve legal protection. The main focus of this study is to evaluate whether systemic discrimination by the federation can be categorized as an unlawful act that goes beyond civil disputes, particularly in terms of abuse of institutional power and neglect of legal obligations to provide a safe and equal work environment.